Solid-state self-healing systems: the diffusion of healing agent for healing recovery - Md Jamil, M.S.; Jones, F.R.; Muhamad, N.N.; Makenan, S.M. (Universiti Kebangsaan Malaysia, 2015)
A clear understanding on the fundamental mechanism in solid state self-healing resin system might significantly improve the optimization of healing performance. The focus of this study was to prove the diffusion (through thermal inter-diffusion) of a linear healing agent within the network matrix resin. The results had demonstrated that 45 to 21 percentage recoveries in fracture toughness (K1C) were observed within the third healing cycles of the healable resin. Based on the optical microscopy, scanning electron microscopy (SEM) and time-of-flight secondary ion mass spectrometry (ToF-SIM) analyst; the diffusion of healing agent was also demonstrated by the change in the morphology and chemical images of the healing agent on the fracture surface specimen, before and after healing process.